Analisis Tingkat Stres Mahasiswa Keperawatan Dalam Mengikuti Sistem Pembelajaran Blok - Theresia Sunarni; Achmad Husaini; Yohanes Dicka Pratama (Universitas Katolik Musi Charitas, 2017)
Application of block system can give positive and negative impact to the students. Evaluation of the implementation of the block system needs to be done to determine the impact of the system applied to the students. Similarly, the impact of the implementation of the block system in Departement of Nursing FiKes UKMC which has started running from 2013 and has never been evaluated. The stress level in this study was measured using the scale of Depression Anxiety and Stress Scale 42 (DASS 42). The measurement scale of DASS 42 contains 42 statements relating to the level of depression, anxiety and stress of a person. The stress statement contained in DASS 42 was modified, so it could illustrate the state of the research subjects. Data collection in the form of questionnaires distributed to students of Departement of Nursing FiKes UKMC as much as 140 respondents. The results of the questionnaire showed that the average respondent's stress level was 12.22, which means having a normal stress level. Statistical analysis using correlation test is used to know the relationship between each variable. The results of the first correlation test relating to gender and stress levels generated correlation coefficient sebasar -0.037 (p = 0.668). Results of the second correlation test between the level of study with stress level generated coefficient correlation sebasar -0.032 (p = 0.710). Results of the third correlation test between GPA with stress level resulted in correlation coefficient of 0.011 (p = 0.893). The last correlation test results between the block system with the stress level with the correlation coefficient value sebasar -0.024 (p = 0.778). From the results of this test obtained all p-values for four hypotheses greater than 0.05, then concluded gender, level of force, and system block is not associated with student stress levels.